(3efMI GdSdhc aj TQM JMaI Gdedhcs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3GdQGRj , Rjf GdOjf eMeO Hf TeS GdOjf CHj HcQ Hf YHO GdbGOQ GdMfaj GdQGRj,J (B666 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdYHO GdabjQ Edi QHg GdZfj CHG eMeO eMehO Hf CMeO GdYjfj GdMfaj jbhd deG hbaJ ai GdOjGQ GdeUQjI OjGQ NjQ hYde s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B112s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B375s
Keywords: (3Gdabg GdMfajs